Shallow 3-5 m snow core density over Djupranen Ice Rise, Leningradkollen Ice Rise, and Nivlisen Ice Shelf, central Dronning Maud Land, Antarctica - Pratap, Bhanu; Matsuoka, Kenichi; Meloth, Thamban (Norwegian Polar Institute, 2021)
The dataset consists of in-situ snow-core density measurements. The depth of these snow cores ranges from 3-5 m. These cores were collected over Djupranen and Leningradkollen ice rises and over the Nivlisen Ice Shelf, Dronning Maud Land.